Assessing environmental impact and farmers’ awareness in irrigated and rainfed rice farming for sustainable agriculture in Yogyakarta, Indonesia - Rozaki, Zuhud; Kamarudin, Mohd Fauzi; Kiloes, Adhitya Marendra; Triyono; Nur Rahmawati; Wibisana, Dharend Lingga (International Information and Engineering Technology Association, 2024)
The agricultural sector still playing a significant role in Indonesia's economy; however, it also has an environmental impact, particularly due to the use of chemicals. Yogyakarta is one of the regions in Indonesia with substantial rice production, but unfortunately the awareness regarding the environmental impact of the rice farming is still low. Therefore, this study aims to analyze the environmental impact of irrigated and rainfed rice farming systems in Yogyakarta, as well as the farmers' awareness of the environmental consequences of their farming practices. This study result can help to raise the awareness of environmental impact from rice farming. Data were collected through interviews with 150 irrigated rice farmers in Sleman Regency and 100 rainfed rice farmers in Gunungkidul Regency. The analytical tool used for environmental impact assessment was the Life Cycle Assessment (LCA) approach, and awareness was analyzed descriptively. Environmental awareness revealed relationships with farmer characteristics such as age, income, and land area. The environmental impact analysis indicated that irrigated farming has a lower total impact (23 Pt) compared to rainfed farming (25.7 Pt). In the climate change impact category, irrigated rice farming had a lower value of 6.34 Pt compared to rainfed land of 11.3 Pt. Although the environmental impact produced is relatively small compared to the industrial sector, it still needs attention from relevant stakeholders to ensure that the environmental impact of rice farming does not develop in a more negative direction.